Use of the extended pectoralis major myocutaneous flap as a wrap-around for mediastinal tracheal repair. (December 2021) - Tan, Grace Hui-Min; Ong, Boon-Hean; Kok, Yee-Onn; Tan, Bien-Keem
Summary: Persistent tracheoesophageal fistulas requiring flap repair of the trachea in the mediastinum are uncommon. A 44-year-old man developed a 5 cm x 2 cm persistent posterior tracheal defect after failed tracheo-esophageal fistula repair. The defect was patch repaired using the de-epithelialized skin paddle of an extended pectoralis major flap tunneled into the mediastinum. The use of cross-field ventilation, second rib removal and an anterior tracheostomy slit were crucial for posterior tracheal repair. No major complication occurred. The patch repair with the de-epithelialized skin paddle of pectoralis major flap mucosalized in 2 weeks and the patient was discharged one month postoperatively. The extended skin paddle of the pectoralis major flap was a useful method for tracheal wrap-around reconstruction.